2016
DOI: 10.1108/ijwhm-04-2015-0021
|View full text |Cite
|
Sign up to set email alerts
|

Who let the dogs in? A look at pet-friendly workplaces

Abstract: Purpose – The purpose of this paper is to present an overview of the pet-friendliness trend, because despite its growth, there has been little research on the benefits and potential risks of pet-friendly workplaces. Design/methodology/approach – A general review is provided on pet ownership figures in North America and the benefits and drawbacks of pet ownership. Pet-friendly policies and practices are described, highlighting their poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 17 publications
(25 reference statements)
1
27
0
Order By: Relevance
“…Here, we observed that employees who “often” and “sometimes” took their dog to work scored high on friendship acuity within the office, whereas individuals who “never” took their dog to work scored average, being significantly lower than employees in the “often” group. This supports previous studies which suggest that a perceived benefit of allowing dogs in the office is increased social interaction (39, 41, 46, 81). Since social support is related to stress, quality of life and working performance (8284), increasing feelings of support are likely to bring a range of work-related benefits.…”
Section: Discussionsupporting
confidence: 91%
“…Here, we observed that employees who “often” and “sometimes” took their dog to work scored high on friendship acuity within the office, whereas individuals who “never” took their dog to work scored average, being significantly lower than employees in the “often” group. This supports previous studies which suggest that a perceived benefit of allowing dogs in the office is increased social interaction (39, 41, 46, 81). Since social support is related to stress, quality of life and working performance (8284), increasing feelings of support are likely to bring a range of work-related benefits.…”
Section: Discussionsupporting
confidence: 91%
“…For example, attending frequent and unpredictable medical appointments as part of eldercare may require different flexibility from generally more predictable childcare arrangements. Furthermore, Wilkin, Fairlie, and Ezzedeen () observe that care of pets requires time and energy and because they are frequently considered as part of the family, work‐life policies should be extended to include them. This may be of particular relevance in countries where pet ownership is common such as the USA, United Kingdom, Brazil, and Argentina (GFK, ) and especially for types of pets that require a significant time commitment from their owners.…”
Section: “Life”—capturing Contemporary Life Worldsmentioning
confidence: 99%
“…One strategy for improving morale in the workplace and protecting against the potential for burnout is offering animal-assisted support programs for employees. Evidence suggests that such programs can have significant positive impacts on employee well-being, and have been associated with reductions in workplace stress and absenteeism, and improvements in employees' mood, health, productivity, job satisfaction, and work quality [25][26][27][28]. Animal-assisted support programs have been successfully offered in select work settings (e.g., office settings, manufacturing, sales) [25,26]; however, there is limited literature to-date assessing the impacts of animal-assisted support on the well-being of healthcare employees working in clinical settings [29].…”
Section: Introductionmentioning
confidence: 99%